Psychoeducational Intervention for Family Caregiver Burden in Stroke Patients Care - Tri Antika Rizki Kusuma Putri; Wisnu Ramadita; Eva Supriatin; Suci Noor Hayati (Risenologi, 2022)
Stroke rehabilitation is a long and complicated process that the majority of rehabilitation to be completed once the patient returns home (community-based stroke rehabilitation). A caregiver supports a stroke survivor in performing daily activities. Because of that responsibilities,caregiver feels physically and psychologically drained. The aim of this study was to find out the effects of psychoeducation on stroke patients' caregiver burden. The study used a purposive random sample technique with a total of 34 respondents to perform a quantitative study with a quasi-experimental design of two groups pre- and post-test in July 2021 in West Java. Zarit Burden Interview (ZBI) questionnaires were used to collect data of caregiving burden. The results of this study indicate that there was a significant difference between the intervention and control groups using the paired t-test (p=0.002) and a significant effect value utilizing the ANCOVA test (p=0.000). The Conclusion are Psychoeducation has a considerable impact on stroke patients' caregiver burden. In caring for stroke patients at home, a nurse can provide psychoeducation and caregiver supplies.